Sejarah Melayu the Malay annals - Leyden, John 1775-1811 (Silverfish Malaysian classics, 2012)
From the period at which Europeans first visited these islands, their civil history may be summed up in few words; it is included in that of their commerce. The extensive trade of these islands had long collected at certain natural and advantageous emporias; of these, Bautian, Achau, Malacca and Macasser were the principal. When we consider the extent of this unparalleled archipelago; the vanity and peculiar character of its people; the infinity of its resources; its contiguity to China and Japan, the most populous region of the earth; and the extraordinary facilities it affords to commerce, from the smoothness of its seas, the number and excellence of its harbours, and the regularity of its monsoons; it would be vain to assign limits, or to say how far and wide the tide of commerce might not have flowed, or how great the progress of civilization might not have been, had they been allowed to pursue their free and uninterrupted course, protected and encouraged by a more enlightened and liberal government.